THE INFLUENCE OF THE DELIVERY CYLINDER OF RING SPINNING MACHINE ON YARN QUALITY INDICATORS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article investigates the influence of the flutes (grooves or notches) on the surface of the delivery cylinder (i.e., the final drafting pair) in a ring spinning machine on yarn quality. The study examines the geometric shape, depth, spacing, and orientation of the fluted cylinders as variable parameters and analyzes their impact on key yarn quality indicators—strength, elongation, hairiness, and unevenness. Experimental work was conducted using yarns made from natural fibers (cotton). The obtained results demonstrate that properly designed fluted cylinders ensure controlled fiber movement, improving yarn uniformity and reducing hairiness. At the same time, incorrect flute parameters may lead to fiber breakage and degradation of yarn quality. The article concludes with recommendations for optimal flute geometry and parameters.